GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 5076 species occurrences available in GBIF matching the query: TaxonKey: Chenopodium vulvaria L. HasCoordinate: true HasGeospatialIssue: false. The dataset includes 5076 records from 106 constituent datasets: 315 records from Botanical Society of the British Isles - Vascular Plants Database. 6 records from University of Vienna, Institute for Botany - Herbarium WU. 3 records from New records in vascular plants alien to Kyrgyzstan. 2 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 4 records from Naturalis Biodiversity Center (NL) - Botany. 8 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 4 records from FLORIVON. 1 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 1 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 88 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 367 records from published_chenopodium_vulvaria_observations. 1 records from SA Flora (BDBSA). 1 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 713 records from FlorKart - FlorenKartierung Gefaesspflanzen. 27 records from OHN. 5 records from Données ONF Faune-Flore-Fonge. 1 records from Geneva Herbarium – Burnat Herbarium (G-BU). 42 records from Australia's Virtual Herbarium. 418 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 1 records from Herbier de Strasbourg. 1 records from Vascular Plant Herbarium, UiB. 1 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 1 records from Natural History Museum Maastricht (NL) - Herbarium. 30 records from Consortium of California Herbaria. 1 records from Collection botanique Le Grand A. (BOUM). 6 records from BioGIS - Vascular plants - INPA database. 191 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 3 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 13 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from naturgucker. 2 records from MfN - Fossil plants (Cenophytic). 2 records from Dutch Vegetation Database (LVD). 2 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 8 records from IBF Monitoring of Vascular Plants. 1 records from Tropicos Specimen Data. 1 records from Naturhistorisches Museum Mainz, Botanical Collection. 33 records from Natural History Museum (London) Collection Specimens. 34 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 12 records from Natural History Museum, Vienna - Herbarium W. 7 records from Flora-On: occurrence data of the flora of mainland Portugal. 4 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 2 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 22 records from The Himalayan Uplands Plant database (HUP Version 1). 4 records from Australian National Herbarium (CANB). 31 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 6 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 34 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 6 records from Herbario de la Universidad de Almeria. 20 records from Jardín Botánico de Córdoba: Herbarium COA. 12 records from Aranzadi Zientzi Elkartea. 11 records from CIBIO, Alicante:ABH-GBIF. 5 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 4 records from Herbario de la Universidad de Sevilla. 2 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 5 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 6 records from Institut Botanic de Barcelona, BC. 4 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 1 records from Auckland Museum Botany Collection. 2 records from Vascular Plant Collection. 4 records from DAV UC Davis Center for Plant Diversity. 1 records from Herbarium (UNA). 11 records from NSW herbarium collection. 1 records from Herbarium Berolinense. 77 records from Herbarium Willing. 1 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 250 records from Observations du Conservatoire botanique national du Bassin parisien.. 26 records from Israel Nature and Parks Authority. 1 records from Institut Botanic de Barcelona, BC-Histórico. 6 records from Impetus - Herbarium Hamburgense. 224 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 49 records from BioGIS - Vascular plants - A. Danin's grid database. 2 records from Biodiversitätsdatenbank des Landes Salzburg. 41 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 8 records from Field Museum of Natural History (Botany) Seed Plant Collection. 12 records from Belgian IFBL Flora Checklists (1939-1971). 40 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 1 records from Perchtoldsdorfer Heide. 231 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 2 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 6 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 23 records from Biological and palaeontological collection and observation data MNHNL. 10 records from Herbarium Senckenbergianum (FR). 19 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 847 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 158 records from Lund Botanical Museum (LD). 2 records from Geographically tagged INSDC sequences. 12 records from Carnet en Ligne. 1 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 3 records from All observations extracted from the Flora of Northumberland and Durham 1831. 1 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 1 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 3 records from Vascular Plant Herbarium, Trondheim (TRH). 5 records from Données ONF Faune-Flore-FOnge. 1 records from Vascular Plants, Field notes, Oslo (O). 344 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 5 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 2 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 29 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 4 records from Allan Herbarium (CHR). 9 records from Vascular Plant Herbarium, Oslo (O). 51 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 1 records from The Flora of County Waterford. 8 records from Geneva Herbarium – General Collection (G). 2 records from Instituto de Botánica Darwinion. 1 records from Nijmegen Natural History Museum (NL) - Herbarium. 1 records from CAS Botany (BOT).
Keywords: GBIF; biodiversity; species occurrences